Training for Mental Health Volunteers of People Living with Schizophrenia in the COVID-19 Pandemic in Bangkalan City - Julia Dian Christiani Adi Santoso; Joewen Sarliency Manafe; Dayu Triana Rahmawati; Sheila Maryam Gautama; Azimatul Karimah (Jurnal Psikiatri Surabaya, 2023)
Introductions: The global coronavirus-19 (COVID-19) pandemic disproportionately burdens people with schizophrenia and related disorders. Access to mental health providers in rural areas was still far from expected. People with schizophrenia in low and middle-income countries, including Bangkalan City, often lack access to evidence-based treatments. We hypothesized that psychoeducation might improve Mental Health Volunteers' (MHV) knowledge and skills to help people with schizophrenia in rural areas. Furthermore, we want to identify the obstacles and practical solutions essential to improving the community's mental health in Bangkalan City. Methods: The total participants were 134 MHV from the Department of Health, Bangkalan City. The data was collected in pretest and posttest on each workshop session and Focus Group Discussion (FGD). Results: There were significant improvements in the knowledge and skills about Schizophrenia of MHVs and programmers from the Department of Health, Bangkalan City (p<0.01). The three most common problems raised in FGD were communication with people with schizophrenia and their families due to health protocols, appeals from community leaders contrary to health policies, and family conflicts. Conclusions: Training for MHV in the Department of Health, Bangkalan City, has improved their understanding of schizophrenia and its interventions, their communication skills with people with schizophrenia and their families, and their skills to handle psychiatric emergencies related to schizophrenia. The three most common problems and the solutions were agreed upon during FGD.